The Parkam exploration district, Kerman, Iran: Geology, alterations, and delineation of Cu- and Mo-mineralized zones using U-spatial statistic with associated software development - Ghannadpour, Seyed Saeed; Hezarkhani, A.; Sabet-Mobarhan-Talab, A. (Zhongguo Dizhi Daxue, 2017)
The Parkam exploration district represents an area of approximately 4 km2 located 50 km north of Shahr-E-Babak (Kerman Province, Iran), and has several traces of old copper mining and smelting activities. This area lies in the Kerman Copper Belt which is part of the larger Sahand-Bazman igneous and metallogenic zone hosting numerous known porphyry copper deposits and systems. The geology of the Parkam exploration district demonstrates that the area contains a diorite-type porphyry copper system hosted by volcanic and pyroclastic rocks of predominantly andesitic composition. Based on field and microscopic investigation, it was determined that the dominant types of alteration were propylitic, phyllic, argillic, and potassic, and the alteration map of the study area was produced. Expect for the propylitic alteration which was observed mainly in the host rocks, the other types of alteration are associated mainly with the dioritic subvolcanic body. Accompanied by subordinate amounts of primary sulfides, fracture-filling malachite is widespread in the potassic and phyllic zones and comprises the dominant style of mineralization at the surface of the porphyry system. Lithogeochemical data resulting from 377 samples were analyzed, and the results of background and anomaly separation by means of conventional and the U-spatial statistic method were compared. The Cu and Mo mineralizations were subsequently delineated using the U-spatial statistic. The delineated Cu mineralization is closely associated with the defined zone of potassic alteration, which is also consistent with the field and microscopic observation of the Cu mineralization in this alteration zone. The Mo mineralization delineated by the U-statistic method is mostly associated with the phyllic alteration and is spatially conformable with the zone defined for it. The source code for a software program, which was developed in the MATLAB programming language in order to perform the calculations of the U-spatial statistic method, is additionally provided. This software is compatible with geochemical variates other than Cu and Mo and can be used in similar exploration projects.